2015
DOI: 10.1007/s10567-015-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

Observational Tools for Measuring Parent–Infant Interaction: A Systematic Review

Abstract: The quality of the parent-infant interaction is essential for the infant's development and is most objectively measured by observation. The existing observational tools for assessing parent-infant interaction were identified and described, and their psychometric soundness was evaluated. Twenty electronic databases from inception through June 2013 were searched. Validity was evaluated in five domains (test content, response process, internal structure, relations to other variables, and consequences). Of the 23,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
102
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 45 publications
4
102
0
2
Order By: Relevance
“…Biringen et al conducted a selective review of EA studies and reported strong inter-rater reliability [22], as well as good validity, in its relation with both parent (such as well being, self efficacy) and child outcomes (such as emotion regulation, positive affect, social competence). An exhaustive review by Lotzin et al on parent-child interaction measures (2015) indicates that the EA Scales are the most commonly used measure of observed parent-child relationships in the field, and is used in the US for all the major subcultures, as well as some 25-30 countries [23]. This concept is different than "emotional intelligence" in that it is not a trait, but a quality of the relationship between two people.…”
Section: Measurement Of Compassionate Behavior Through a Multidimensimentioning
confidence: 99%
“…Biringen et al conducted a selective review of EA studies and reported strong inter-rater reliability [22], as well as good validity, in its relation with both parent (such as well being, self efficacy) and child outcomes (such as emotion regulation, positive affect, social competence). An exhaustive review by Lotzin et al on parent-child interaction measures (2015) indicates that the EA Scales are the most commonly used measure of observed parent-child relationships in the field, and is used in the US for all the major subcultures, as well as some 25-30 countries [23]. This concept is different than "emotional intelligence" in that it is not a trait, but a quality of the relationship between two people.…”
Section: Measurement Of Compassionate Behavior Through a Multidimensimentioning
confidence: 99%
“…EEG/ERP is more feasible and provides optimal temporal resolution, but poor spatial resolution. Finally, directly observed measures of empathic behavior such as a social discounting task previously linked to MSDP ( 139 ) and postpartum observations of mother–infant interactions ( 140 ) may also be useful.…”
Section: A Roadmap For Research Using An Em Approachmentioning
confidence: 99%
“…There are a number of observational measures available to researchers and practitioners to assess early parent–child interactions, but these measures target a broad range of constructs (i.e., dyadic synchrony, maternal responsivity/sensitivity, emotional availability, affect, learning support, intrusiveness), and subsequently utilize different units for coding target behavior (Aspland and Gardner 2003 ; Lotzin et al 2015 ). Coding schemes are typically classified into two categories; macro or micro (Dishion et al 2017 ; Rosenberg et al 1986 ).…”
mentioning
confidence: 99%
“…Due to their complexity micro observational schemes require extensive training, but it is argued that these measurements of parent–child dynamics are more sensitive to change following intervention (Dishion et al 2017 ; Morawska et al 2014 ). Due in part to methodological variation between measures, there is little agreement in the literature as to which is accepted as the single standard for measuring parent-infant interaction (Lotzin et al 2015 ). Consequently, when researchers and practitioners are selecting the most appropriate measure to be used for their purpose it is argued that careful consideration of a measure’s reliability and validity should be taken into account (Lotzin et al 2015 ; Rosenberg et al 1986 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation